Efektivitas Implementasi Teori Behaviorisme dalam Proses Pembelajaran - Ananda, Zavira Trya; Yusuf, Arbaiyah; Pitaloka, Anna Fadhila (MASALIQ, 2023)
This article discusses the application of behaviorism learning theory and its advantages and disadvantages. The method used in writing this article is a literature review system. In behaviorism learning theory there are basic concepts in learning, namely the interaction between stimuli and responses. The application of behaviorism learning theory will enable teachers to be more sensitive to learning situations and circumstances. Besides that, behaviorism learning theory is suitable for young children who still need adult supervision. However, behaviorism learning theory is often criticized because this learning theory cannot explain complex learning situations